JUDGES' CONSIDERATIONS IN ISSUE-MAKING DECISIONS REGARDING THE LENGTH OF SENTENCES FOR PERPETRATORS OF CHILD INDEMNITY (STUDY OF LUBUKPAKAM DISTRICT COURT DECISION NO. 2044/PID.SUS/2021/PN.LBP JO MEDAN HIGH COURT DECISION NO. 2093/PID.SUS/2021/PT.MDN JO S - Spesio Panjaitan, Kevin Theodosus; Mulyadi, Mahmud; Alsa, Abdul Aziz (Penerbit Lafadz Jaya, 2025)
The perpetrators of child molestation crimes deserve to be given a fairly high sentence, for example, as stated in Law No. 17 of 2016 concerning Government Regulation in Law No. 1 of 2016 concerning the Second Amendment to Law No. 23 of 2002 concerning Child Protection into Law, where in Article 81 A paragraph (3) there is a criminal sanction in the form of chemical castration for perpetrators of child molestation. However, in reality, in law enforcement related to child molestation crimes where children are victims, not all perpetrators are given the maximum or severe sentence. The sentence given to perpetrators of child molestation crimes is reduced or not punished severely. This is as stated in the Decision of the LubukPakam District Court No. 2044/Pid.Sus/2021/PN.Lbp Jo Decision of the Medan High Court No. 2093/Pid.Sus/2021/PT.Mdn Jo Decision of the Supreme Court No. 2909K/Pid.Sus/2022